1984
DOI: 10.1177/036354658401200613
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic steroids: A review of the literature

Abstract: The use of anabolic steroids by athletes is controversial. On the one hand, many athletes believe that steroids improve athletic performance and thus provide an advantage to those who use them. On the other hand, the medical and scientific communities believe that inadequate scientific data exist to support the claim that anabolic steroids can improve athletic performance while overwhelming scientific data demonstrate their deleterious effects. Therefore, a large information and credibility gap concerning anab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
137
1
19

Year Published

1990
1990
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 385 publications
(160 citation statements)
references
References 73 publications
(5 reference statements)
3
137
1
19
Order By: Relevance
“…One review of 13 studies of athletes using steroids found that 34% of the individuals reported behavioral side effects (Haupt & Rovere, 1984). Some studies seem to indicate that heavy use seems particularly likely to elicit aggressive reactions (Conacher & Workman, 1989;Pope & Katz, 1990), but there are some studies that report negative findings (Bahrke et al, 1990;Bahrke, Wright, Strauss, & Catlin, 1992).…”
Section: Anabolic-androgenic Steroidsmentioning
confidence: 99%
“…One review of 13 studies of athletes using steroids found that 34% of the individuals reported behavioral side effects (Haupt & Rovere, 1984). Some studies seem to indicate that heavy use seems particularly likely to elicit aggressive reactions (Conacher & Workman, 1989;Pope & Katz, 1990), but there are some studies that report negative findings (Bahrke et al, 1990;Bahrke, Wright, Strauss, & Catlin, 1992).…”
Section: Anabolic-androgenic Steroidsmentioning
confidence: 99%
“…One of the commonest side effects is sodium retention which gives rise to water retention and then oedema [32,62]. Water retention and increased erythropoesis contribute to an increase in blood volume [42,62] and also to the increased weight gain that occurs following anabolic steroid administration [32,43].…”
Section: Anabolic Steroid Side Effectsmentioning
confidence: 99%
“…One of the commonest side effects is sodium retention which gives rise to water retention and then oedema [32,62]. Water retention and increased erythropoesis contribute to an increase in blood volume [42,62] and also to the increased weight gain that occurs following anabolic steroid administration [32,43]. Much of the initial increase in muscle size and bulk that occurs following AS administration is due to the retention of water in the muscle tissue and not to an increase in protein content or muscle fibres [32,63].…”
Section: Anabolic Steroid Side Effectsmentioning
confidence: 99%
See 2 more Smart Citations